USERS’ SENSE OF EMPOWERMENT, COMMUNICATIVE BEHAVIOR, AND PUBLIC ENGAGEMENT ON INSTAGRAM: AN EXAMINATION OF THE #BLACKOUTTUESDAY CONVERSATIONS - Zaher, Zulfia; Dejmanee, Tisha; Weber, Kirsten (AoIR Selected Papers of Internet Research, 2023)
#BlackoutTuesday was a digital action devised as part of the unprecedentedly large Black Lives Matter protests in 2020. This study builds on Black Lives Matter research through its three main objectives: To test three new independent variables —race, gender, and source — in determining the demonstration of users’ empowerment; to test race, gender, and source to determine users’ communicative behavior on Instagram; and, to investigate the connection between source types and user engagement on Instagram. We conducted quantitative content analysis to address the research questions. Using CrowdTangle we collected ten thousand Instagram posts containing #BlackOutTuesday published on June 2, 2020. This study is based on 1250 posts randomly selected from the original sample. This study tested eight hypotheses. Using a series of Chi-Square tests, the results revealed that the users’ gender, race, and source types were significantly associated with their sense of empowerment and communicative behavior regarding #BlackOutTuesday conversation on Instagram. This study also investigated the factors that influenced higher engagement. Employing a One-Way ANOVA, the results showed that source types, particularly celebrities and for-profit and media organizations, generated more Likes. We also found that negative emotions created more Likes and Comments. However, the results did not support the association of post structure with higher engagement .